SUFFIXES は(WA) AND が(GA) IN JAPANESE: ANALYSIS OF SYNTACTIC AND SEMANTIC DIFFERENCES - Amirova Yulduz Qodirjon qizi (Web of Journals Publishing, 2026)
This article analyzes the negative impact of several factors on road capacity. The factors causing traffic jams were studied and analyzed based on the results of research and inspections.
Keywords: Traffic jams, road traffic accidents, research on the impact on capacity, hazards, trees, buildings, winter and summer, driver, sharply limiting capacity, Road surveillance.